A class of double phase problem without Ambrosetti-Rabinowitz-type growth condition: infinitely many solutions - Ge, Bin; Han, Yuhang; Cao, Qinghai; Ren, Haixin (Topological Methods in Nonlinear Analysis, 2024)
This paper concerns with a class of double phase problem without Ambrosetti-Rabinowitz-type growth condition.Under reasonable hypotheses, we establish the existence of infinitely many solutions by using thevariant fountain theorems due to Zou \cite{71}.